Soluble Prefusion Closed DS-SOSIP.664-Env Trimers of Diverse HIV-1 Strains - Joyce, M. Gordon; Georgiev, Ivelin S.; Yang, Yongping; Druz, Aliaksandr; Geng, Hui; Chuang, Gwo-Yu; Kwon, Young Do; Pancera, Marie; Rawi, Reda; Sastry, Mallika; Stewart-Jones, Guillaume B.E.; Zheng, Angela; et al. (Cell reports (Cambridge), 2017)
The elicitation of autologous neutralizing responses by immunization with HIV-1 envelope (Env) trimers conformationally stabilized in a prefusion closed state has generated considerable interest in the HIV-1 vaccine field. However, soluble prefusion closed Env trimers have been produced from only a handful of HIV-1 strains, limiting their utility as vaccine antigens and B cell probes. Here, we report the engineering from 81 HIV-1 strains of soluble, fully cleaved, prefusion Env trimers with appropriate antigenicity. We used a 96-well expression-screening format to assess the ability of artificial disulfides and Ile559Pro substitution (DS-SOSIP) to produce soluble cleaved-Env trimers; from 180 Env strains, 20 yielded prefusion closed trimers. We also created chimeras, by utilizing structure-based design to incorporate select regions from the well-behaved BG505 strain; from 180 Env strains, 78 DS-SOSIP-stabilized chimeras, including 61 additional strains, yielded prefusion closed trimers. Structure-based design thus enables the production of prefusion closed HIV-1-Env trimers from dozens of diverse strains. [Display omitted] •Identified 20 strains of HIV-1 compatible with prefusion DS-SOSIP stabilization•Utilized a chimeric strategy to increase the number of stabilized strains•Produced prefusion closed DS-SOSIP-stabilized Env chimeras from 81 strains•Stabilized Env chimeras should have utility as HIV-1 immunogens and B cell probes Joyce et al. use a structure-based chimeric strategy to produce prefusion closed Env trimers from 81 strains of HIV-1 encompassing all major clades. These soluble Env trimers should have utility as B cell probes and HIV-1 immunogens, thereby enabling both antibody identification and vaccine development.